Analyst underreaction and the post‐forecast revision drift - Chen, Po‐Chang; Narayanamoorthy, Ganapathi S.; Sougiannis, Theodore; Zhou, Hui (Journal of business finance & accounting, 2020)
The post‐forecast revision drift (PFRD), the phenomenon of delayed stock price reactions to analyst forecast revisions, is a well‐documented market anomaly. Prior research attributes PFRD to underreaction by investors to analyst forecast revisions. This study investigates the role of the analyst forecast revision process itself in the PFRD anomaly. Using a large sample of US firms, we confirm prior findings of a positive serial correlation (momentum) in individual analysts’ revisions to their earnings forecasts and, based on both indirect and direct tests, document a positive association between this momentum and PFRD. Further analyses reveal that both the forecast revision momentum and PFRD vary in similar ways with respect to the nature of the news driving the revisions and the information environment. Collectively, our findings show that underreaction by individual analysts in the forecast revision process is an important contributor to the PFRD phenomenon.